Of time and the enterprise : North American family farm management in a context of resource marginality : based on a decade of research in the Province of Saskatchewan, Canada - Bennett, John W. (John William), 1915-2005 (University of Minnesota Press, 1982)
Of Time and the Enterprise was first published in 1982. Of Time and the Enterprise is the result of 12 years' research in the Canadian sector of the northern Great Plains -- a 7,000-square-mile region that was one of the last areas in North America to be populated by agricultural settlers. This late settlement permitted a reconstruction of the area's history and economic and social development unparalleled in the literature. This book has several dimensions. It is, first, a meticulous study of the North American family farm. Bennett considers such aspects of the family farm as the ways that fa.